2012
DOI: 10.21861/hgg.2012.74.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Issues in the Regional Development of Tourism in Croatia

Abstract: The aim of this research is an analysis of the tourism development of the smallest administrative units (towns and municipalities) as well as their typology within the Croatian tourism regions. The methodological approach is based on GIS analysis of seven relevant indicators of tourism development; this is a tool for defining typology. Such an approach helps in determining the conclusion concerning the role that tourism plays in each administrative unit inside the respective five Croatian tourism regions. Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Therefore, polarised tourism development is also an occurrence in countries with a lower level of tourism development. The comparison with neighbouring Croatia (Curić et al, 2013) showed that the differences between tourism developments of certain regions were almost identical, and even greater in the case of certain indicators. Primjetno je da su u Bosni i Hercegovini jače naglašeni problemi monocentričnoga turističko-ga razvoja na regionalnoj razini.…”
Section: Specifics Of the Problems Of Tourism Development Of Bosnia Amentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, polarised tourism development is also an occurrence in countries with a lower level of tourism development. The comparison with neighbouring Croatia (Curić et al, 2013) showed that the differences between tourism developments of certain regions were almost identical, and even greater in the case of certain indicators. Primjetno je da su u Bosni i Hercegovini jače naglašeni problemi monocentričnoga turističko-ga razvoja na regionalnoj razini.…”
Section: Specifics Of the Problems Of Tourism Development Of Bosnia Amentioning
confidence: 94%
“…They can be seen both at the national (regional) level and within each tourism region. The geographic concentration of tourism flow within a single or small number of tourism regions is a characteristic of almost all countries with developed tourism (Curić et al, 2013). On the other hand, there is a question of the extent to which such geographical disparities of tourism exist in countries that are not among the most important tourism destinations in the world.…”
Section: Introductionmentioning
confidence: 99%
“…As indicators for pressures, they singled out: arrivals in hotels and similar establishments, non-residents, arrivals in hotels and similar establishments, residents, arrivals in other establishments, residents, airport rank, arrivals of tourists/km 2 , nights spent/km 2 , arrivals of tourists/1000 people, nights spent/1000 people, and number of congresses held in the region. Curić, Glamuzina and Opačić (2012) measured the level of tourism development of cities/towns and municipalities in Croatia using GIS analysis of seven tourism indicators: number of beds, number of arrivals, number of international arrivals, overnight stays, international overnight stays, number of arrivals per surface area of local self-government units, and number of arrivals per capita. Glamuzina, Madžar and Putica (2017) applied a nearly identical set of indicators in their research of regional aspects of tourism development of Bosnia and Herzegovina.…”
Section: Introductionmentioning
confidence: 99%
“…The Town of Novalja on the island of Pag is located in the region of the northern Croatian littoral as its northern (Kvarner) part is more developed for tourism than its southern (Dalmatian) part (Curić et al, 2013). In the region of the south Croatian littoral, or Dalmatia, there are towns and municipalities with four of them located in north Dalmatia: Nin, Šibenik,Vodice and Zadar.…”
Section: Introductionmentioning
confidence: 99%
“…GIS analysis was also used for regional tourist differentiation for units of local and regional government and tourist regions in Croatia and Bosnia and Herzegovina (Curić et al, 2012;Glamuzina et al, 2017) and also the tourist intensity rate as an indicator when branding destinations in Croatia and abroad (Mikulić et al, 2014;2016).…”
mentioning
confidence: 99%